Selection of phage display peptides against Pasteurella multocida using suspension method of biopanning - KRITIKA DHIAL; MANDEEP SHARMA; SUBHASH VERMA; GEETANJALI SINGH; SANJEEV KUMAR; VIPIN KUMAR GUPTA (Indian Journal of Animal Sciences, 2022)
• multocida contain various surface-associated antigens that could be used as a target for both therapeutics as well as diagnostics. The current study was planned to select ligands using Ph.D.-12 phage display library. This library was amplified and subjected to the alternate selection/subtraction methodology of biopanning using the suspension method in which alternate rounds of positive selection against P. multocida and negative selection against Haemophilus influenzae and Actinobacillus lignieresii were performed. After completing biopanning, out of 48 selected phages, 16 clonal phages were selected for indirect phage ELISA to check their binding efficiency with P. multocida. Out of these 16, five clonal phages bound their target with high intensity giving higher OD values at 450 nm and their binding efficiency was compared with closely related Actinobacillus lignieresii and Hemophilus influenzae using 107 pfu/ml at 450 nm wavelength which was found to be less against these bacteria.